Performance of bulls on Kansas Bull Test - R.R. Schalles; K.O. Zoellner (Kansas Agricultural Experiment Station Research Reports, 1975)
Bulls on summer test gained faster than those on winter test. Breeds from Continental Europe were taller at the shoulder and gained faster than British breeds. Older bulls that were lighter at the start of the test gained slightly faster than younger, heavier bulls, probably because of differences in condition. Adjusted 205-day weight had little relationship to performance; however, weaning weight ratio was positively related to performance on test, indicating that the heaviest bulls at weaning in a herd are most apt to perform best on test.
Keywords: Cattlemen' s Day; 1975; Report of progress (Kansas State University. Agricultural Experiment Station); 230; Beef; Performance; Gain; Weaning weight